Potential Therapeutic Role of Phytochemicals to Mitigate Mitochondrial Dysfunctions in Alzheimer's Disease - Md. Ataur Rahman; MD. Hasanur Rahman; Partha Biswas; Md. Shahadat Hossain; Rokibul Islam; Md. Abdul Hannan; Md Jamal Uddin; Hyewhon Rhim (MDPI AG, 2020)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by a decline in cognitive function and neuronal damage. Although the precise pathobiology of AD remains elusive, accumulating evidence suggests that mitochondrial dysfunction is one of the underlying causes of AD. Mutations in mitochondrial or nuclear DNA that encode mitochondrial components may cause mitochondrial dysfunction. In particular, the dysfunction of electron transport chain complexes, along with the interactions of mitochondrial pathological proteins are associated with mitochondrial dysfunction in AD. Mitochondrial dysfunction causes an imbalance in the production of reactive oxygen species, leading to oxidative stress (OS) and vice versa. Neuroinflammation is another potential contributory factor that induces mitochondrial dysfunction. Phytochemicals or other natural compounds have the potential to scavenge oxygen free radicals and enhance cellular antioxidant defense systems, thereby protecting against OS-mediated cellular damage. Phytochemicals can also modulate other cellular processes, including autophagy and mitochondrial biogenesis. Therefore, pharmacological intervention via neuroprotective phytochemicals can be a potential strategy to combat mitochondrial dysfunction as well as AD. This review focuses on the role of phytochemicals in mitigating mitochondrial dysfunction in the pathogenesis of AD.